Needle-shaped copper-containing carbon nitrogen oxygen sulfur compound crystal and preparation method thereof

By preparing needle-shaped copper-containing carbon-nitride sulfur compound crystals under normal temperature and pressure, the problem of high temperature and expensive equipment required for the preparation of existing copper-based catalysts is solved, and low-cost and efficient catalyst preparation and excellent catalysis are achieved. performance.

CN119386916APending Publication Date: 2025-02-07TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411568102.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing copper-based catalyst preparation methods require high temperature processes or expensive instruments and equipment, resulting in high energy consumption and high preparation costs, limiting the application and promotion of catalysts.

Method used

The method of preparing needle-shaped copper-containing carbon-nitride sulfur compound crystals under normal temperature and pressure is adopted. By adding a coordination agent and a metal salt to the dilute sulfuric acid solution, the process of repeated immersion and residence of elemental copper materials is used to form a needle-shaped crystal catalyst. , and the crystal growth was regulated by ethanol treatment.

Benefits of technology

It realizes efficient preparation of copper-based catalysts under normal temperature and pressure, reduces preparation costs, improves the catalytic performance and stability of the catalyst, and is suitable for reactions such as ORR, HER, CO2RR and VOCs catalytic degradation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386916A_ABST
    Figure CN119386916A_ABST
Patent Text Reader

Abstract

The invention discloses a needle-shaped copper-containing carbon nitrogen oxygen sulfur compound crystal and a preparation method thereof. The needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal can be prepared at normal temperature and normal pressure through the processes of simple substance copper material pretreatment, nonmetal raw material liquid preparation and compound crystal preparation, the microstructure is a needle-shaped crystal, and a plurality of needle-shaped crystals are stacked together to form a loose and porous net structure. The crystal can be regulated and controlled to grow into a more regular prism crystal structure through simple ethanol treatment. The preparation method is simple in process, controllable in condition, safe, efficient, wide in universality and suitable for continuous batch production. The prepared needle-like copper-containing carbon, nitrogen, oxygen and sulfur compound crystal catalyst can be applied to reactions such as catalytic degradation of ORR, HER, CO2RR and VOCs, and the result shows that the prepared catalyst has a good catalytic degradation effect on toluene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic material preparation, and particularly relates to a needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal and a preparation method thereof. Background Art

[0002] Transition metals such as Fe, Cu, Ni, and Pt have special d orbital distributions, which can serve as active centers for catalytic reactions and exhibit excellent CH delocalization capabilities in related catalytic reactions. Among them, Cu-based catalysts have the advantages of low cost and high catalytic activity, and have been used in reactions such as carbon-based small molecule hydrogenation, synthetic ammonia, and catalytic degradation of organic matter.

[0003] In order to further improve the activity of the catalyst, the catalyst can be doped with metal or non-metal elements to change the coordination environment or increase the active center. When the catalyst introduces a second metal component into the single metal site M-Cx structure, on the one hand, the heteronuclear atoms can form different active centers, thereby increasing the active sites of the catalyst and improving the catalytic performance; on the other hand, there is interaction between adjacent metal atoms, and this interaction can adjust the electronic structure of the catalytic active site, thereby effectively improving the catalytic performance. In addition, non-metallic heteroatom doping is also an effective means to improve the activity of the catalyst. The addition of non-metallic elements with different electronegativity and atomic size from C and N atoms can change its electronic structure by adjusting the surrounding non-metallic coordination elements of the M-Cx structure, so that the charge is redistributed, thereby improving the catalytic activity. Commonly used non-metallic elements for doping include B, S, P, Cl, etc. Among them, S atom-doped catalysts are widely used in ORR, HER and CO2RR reactions due to their excellent performance. The existing sulfur-doped catalyst preparation methods mainly include chemical vapor deposition, sol-gel, microwave heating and hydrothermal methods. Zhou et al. synthesized N, S-doped NiSe2 / 3DSNG / NF catalysts on three-dimensional graphene / nickel foam by CVD and hydrothermal method, which showed excellent HER and OER activities in alkaline electrolyte. Luo et al. prepared bimetallic sulfur-doped nickel cobalt selenide catalysts (NiCo-Se 0.2 / CF), exhibiting excellent OER and HER catalytic performance in the water splitting process and having remarkable durability under alkaline electrolyte conditions. Wang et al. synthesized a highly sulfur-doped Cu2O catalyst using CuSO4·3H2O and CuS interlaced precursors by electroreduction, which has a formate selectivity of up to 92% in CO2RR and can reach a maximum of 321 mA cm at a high formate Faradaic efficiency (>80%) in the flow cell test. -2The current density is better than that of most copper-based catalysts without late transition metals. Therefore, it is possible to consider doping S atoms into Cu-based catalysts to improve the electron distribution of active sites and enhance catalyst performance.

[0004] At present, the main methods for preparing copper-based active site catalysts include chemical vapor deposition (CVD), atomic layer deposition (ALD), wet chemical method (impregnation-adsorption method and co-precipitation method), high-temperature pyrolysis method and electrochemical method. These methods generally require high-temperature processes or expensive instruments and equipment during the preparation process, which further increases the cost of catalyst preparation, thus creating certain obstacles to the application and promotion of catalysts. Therefore, in order to solve the problem of high energy consumption in the preparation of copper-based catalysts, it is very necessary to develop a method for preparing copper-based catalysts with high catalytic performance at room temperature and pressure. Summary of the invention

[0005] The purpose of the present invention is to provide a needle-shaped copper-containing carbon, nitrogen, oxygen and sulfur compound crystal at room temperature and pressure and a preparation method thereof in view of the problems existing in the prior art. The present invention is a method for preparing and regulating the growth of a copper-based catalyst that can be applied to reactions such as ORR, HER, CO2RR and VOCs catalytic degradation. The method realizes the synthesis of needle-shaped copper-containing carbon, nitrogen, oxygen and sulfur compound crystals at room temperature and pressure, aiming to provide a new reference for the design, construction and low-energy consumption preparation of copper-based catalysts.

[0006] The purpose of the present invention can be achieved by the following scheme: The present invention provides a method for preparing needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystals, the preparation method comprising the following steps: S1. Non-metallic raw material liquid configuration: Add a complexing agent and a metal salt to a dilute sulfuric acid solution and stir until the solution is clear to obtain a non-metallic raw material solution; S2. Catalyst preparation: The single copper material is completely immersed in the non-metallic raw material liquid, kept there, taken out, and then immersed in new single copper material, and this step is repeated until a large amount of precipitation appears at the bottom of the non-metallic raw material liquid, thereby obtaining a precipitate (catalyst), that is, needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystals.

[0007] As one embodiment of the present invention, the preparation of needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystals is carried out at normal temperature and pressure.

[0008] As an embodiment of the present invention, in step S1, the concentration of the dilute sulfuric acid solution is 0.1 to 1.0 mol / L. Preferably, it is 0.1 to 0.5 mol / L. The dilute sulfuric acid solution is prepared by stirring evenly with a magnetic stirrer until the concentration of the solution drops to room temperature. The magnetic stirring speed is 200 to 800 rpm, preferably 400 to 800 rpm.

[0009] As an embodiment of the present invention, in step S1, the metal salt includes one of tin sulfate (II), tin chloride (II), zinc chloride, and nickel sulfate, and more preferably tin sulfate (II). The ligand includes one of thiourea, ethylenediaminetetraacetic acid (EDTA), and 2-mercaptobenzimidazole (M). The main function of the ligand (a ligand that easily forms a complex with copper ions) and the metal salt (the metal cation of the metal salt is generally a cation of a metal with a metal activity greater than that of copper, and the anion is generally a chloride ion and a sulfate ion) in the non-metallic raw material liquid is to react with elemental copper to form a complex, thereby promoting the formation of copper-containing carbon, nitrogen, oxygen, and sulfur compound crystals in the next step. The metal salt is mainly a compound formed by a cation of a metal with a higher activity than copper and a non-metallic anion. In the non-metallic raw material liquid, the amount of the metal salt is 10 to 100 g / L, and the amount of the ligand is 10 to 70 g / L. The amount of the metal salt is preferably 10 to 50 g / L, and the amount of the ligand is preferably 20 to 60 g / L. The main purpose of the above parameters is to ensure that the single copper material reacts with the ligand and the metal salt under suitable pH conditions, and to ensure that the reaction can continue to occur stably within a certain period of time, thereby improving the efficiency of catalyst preparation.

[0010] As an embodiment of the present invention, in step S2, the single copper material is a material containing a single copper component on the surface. The single copper material is preferably a single copper material with a larger specific surface area. It is preferably one or more of a copper rod, a copper wire, a copper sheet, a copper foil, and a foam copper, and more preferably one or more of a foam copper, a micron copper foil, and a copper sheet. The purpose of selecting the above copper materials is to increase the contact area between the copper material and the solution, thereby increasing the reaction rate.

[0011] The single copper material is preferably one or more of copper wire, copper foil, and copper foam. Other copper materials, such as copper sheets, have a smaller contact area with the solution than preferred materials such as copper foam, and may not react sufficiently, resulting in poor catalyst effect.

[0012] As an embodiment of the present invention, in step S2, the elemental copper material is pretreated before use: the elemental copper material is taken, and the elemental copper material is rinsed with deionized water. After rinsing, the elemental copper material is placed in a cool and ventilated place to allow the elemental copper material to dry naturally.

[0013] As an embodiment of the present invention, in step S2, the residence time is 5 to 25 min, and preferably 5 to 20 min. The number of repetitions is 10 to 100 times, and preferably 10 to 50 times. Repeating this step is to take fresh single copper material and repeat this step, so that the surface single copper and the solution continue to react, and the copper ions in the solution are continuously replenished to ensure the continuous progress of the reaction. In the preparation process of the present invention, after the single copper material is immersed, a layer of tin (zinc, nickel) will be plated on the surface to prevent the copper element inside from further reacting, so the new single copper material is repeatedly immersed, which can ensure that the copper ions are continuously generated on the single copper material, control the reaction process, and continuously generate precipitates, and the morphology is a needle-shaped copper-containing carbon, nitrogen, oxygen and sulfur compound crystal. If copper salt is directly added, the reaction path will be changed so that the target catalyst cannot be generated. For example, when a sufficient amount of copper sulfate solution is added to a solution containing a coordination agent, a milky suspension will be formed, and the resulting precipitate presents irregular clusters, and needle-shaped crystals are not formed, and there is almost no catalytic degradation effect on toluene.

[0014] As an embodiment of the present invention, in step S2, the obtained precipitate (catalyst) is washed and dried. The washing is carried out by washing with deionized water and ethanol in sequence. The deionized water is washed 3 to 5 times, and the ethanol is washed 1 to 3 times. The drying is placed in an oven for vacuum drying, and the vacuum drying temperature of the oven is set to 60 to 100 ° C, and preferably 60 to 80 ° C. The vacuum drying time is 6 to 12 hours, and preferably 7 to 12 hours. The main purpose of the above parameters is to ensure that the reactants react fully and generate a sufficient amount of catalyst to reduce the production of by-products.

[0015] As an embodiment of the present invention, in step S2, the obtained needle-shaped copper-containing carbon, nitrogen, oxygen and sulfur compound crystals are fine light yellow powder (can pass through a 200 mesh sieve). The microscopic morphology of the needle-shaped copper-containing carbon, nitrogen, oxygen and sulfur compound crystals is a needle-shaped crystal, and a plurality of needle-shaped crystals are piled together to present a loose and porous network structure. The single needle-shaped crystal is about 5 to 10 μm long and about 1 to 2 μm wide.

[0016] The catalytic effect of the catalyst of the present invention is related to the material morphology. Generally, the loose porous structure increases the contact area between the reactants and the active sites, and increases the reaction rate; the porous structure is also conducive to improving the mass transfer efficiency of the reactants and products on the catalyst surface, reducing mass transfer restrictions, and increasing the reaction rate. Since the specific surface area of ​​the catalyst with a loose porous structure is increased, the same catalytic effect can be achieved at a lower catalyst dosage, thereby reducing costs.

[0017] As an embodiment of the present invention, the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystals obtained in step S2 are further subjected to ethanol-regulated crystal growth treatment: the precipitate (catalyst) is added to ethanol for immersion, and then centrifuged, and the precipitate is extracted to obtain the precipitate (catalyst) regulated by ethanol treatment, that is, prismatic copper-containing carbon-nitrogen-oxygen-sulfur compound crystals.

[0018] The ethanol soaking time is 10 to 100 min, preferably 20 to 60 min. The centrifugal treatment time is 2 to 10 min, preferably 2 to 6 min, and the rotation speed is 3000 to 12000 r / min, preferably 5000 to 10000 r / min.

[0019] The precipitate (catalyst) obtained after the ethanol treatment is dried. The drying is vacuum drying at a temperature of 60 to 100° C., preferably 60 to 80° C., for 6 to 12 hours, preferably 7 to 12 hours.

[0020] After the needle-shaped copper-containing carbon, nitrogen, oxygen and sulfur compound crystals are treated with ethanol, the needle-shaped compound structure no longer aggregates, and the needle-shaped crystal structure is converted into a more regular prismatic crystal structure, thereby obtaining a prismatic copper-containing carbon, nitrogen, oxygen and sulfur compound crystal. The prismatic crystal is about 20 to 40 μm long and about 10 to 20 μm in diameter.

[0021] Prismatic catalysts may expose specific active crystal faces, have higher catalytic activity for specific chemical reactions, and help improve the selectivity and rate of the reaction. Prismatic catalysts have a single and stable morphology, which is conducive to the large-scale production of high-purity catalysts.

[0022] The present invention also provides a method for preparing a needle-shaped copper-containing carbon, nitrogen, oxygen and sulfur compound crystal obtained by the preparation method and using it as a catalyst in ORR, HER, CO2RR and VOCs catalytic degradation. Compared with the prior art, the present invention has the following beneficial effects: 1) The needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystals prepared by the present invention successfully dope the non-metallic S element into the Cu-based catalyst, and the finished catalyst can be applied to reactions such as ORR, HER, CO2RR and VOCs catalytic degradation.

[0023] 2) The present invention realizes the preparation of needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystals at room temperature and pressure. The process is simple and does not require high-temperature treatment steps, which greatly reduces the preparation cost of Cu-based catalysts and provides a process guide for the processing of S-doped Cu-based catalyst materials.

[0024] 3) The present invention proposes to use ethanol treatment to regulate the growth of copper-containing carbon-nitrogen-oxygen-sulfur compound crystals. The treatment method is simple and the regulation effect is obvious, which provides a process guide for crystal growth regulation and catalyst modification.

[0025] 4) The needle-shaped copper-containing carbon, nitrogen, oxygen and sulfur compound catalyst prepared by the present invention has a good catalytic degradation effect on toluene, and can be used at a reaction temperature of 25 °C and a toluene concentration of 200 mg / m 3 Under the conditions of air velocity of 10000 mL / (g·h) and relative humidity of 30%, the removal rate of toluene can be maintained above 70% within 4 hours. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings: Figure 1 This is a macroscopic image of the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal prepared in Example 1; Figure 2 The SEM morphology images of the needle-shaped copper-containing carbon-nitrogen-oxysulfur compound crystals prepared in Example 2; wherein a is a SEM morphology image magnified 1000 times, b is a SEM morphology image magnified 2000 times, c is a SEM morphology image magnified 3000 times, and d is a SEM morphology image magnified 5000 times; Figure 3 The microscopic morphology of the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal prepared in Example 2; wherein a is a SEM morphology image, and b~f are mapping surface scans; Figure 4 This is a SEM morphology image of the copper-containing carbon, nitrogen, oxygen and sulfur compound crystal after ethanol treatment prepared in Example 3; wherein a is a SEM morphology image magnified 100 times, and b is a SEM morphology image magnified 1000 times; Figure 5 The catalytic degradation effect of the catalyst prepared in Example 1-5 on toluene (reaction temperature is 25 °C, toluene concentration is 200 mg / m 3 , space velocity is 10000 mL / (g·h), relative humidity is 30%)); Figure 6 The catalytic degradation effect of the catalysts prepared in Example 1, Comparative Examples 2 and 4 on toluene (reaction temperature: 25°C, toluene concentration: 200 mg / m 3 , space velocity is 10000 mL / (g·h), relative humidity is 30%)); Figure 7 The milky white suspension formed by directly adding the copper salt solution in Comparative Example 5; Figure 8The SEM morphology images of the precipitates produced in Comparative Example 5 and Example 1; wherein a is the SEM morphology image of the precipitate produced in Comparative Example 5, and b is the SEM morphology image of the precipitate produced in Example 1; Fig. 9 The microscopic morphology of the precipitate produced in Comparative Example 5; a is a SEM morphology image, and b~f are mapping surface scans. DETAILED DESCRIPTION

[0027] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0028] Example 1 Copper foam is used as a single copper material to prepare copper-containing carbon, nitrogen, oxygen and sulfur compounds.

[0029] The specific preparation process is as follows: S1: Pretreatment of single copper material: Take the foam copper material, rinse the foam copper with deionized water, and after rinsing it clean, place the foam copper in a cool and ventilated place to allow the foam copper to dry naturally.

[0030] S2: Non-metallic raw material solution preparation: Prepare 0.5 mol / L dilute sulfuric acid solution, use a magnetic stirrer to stir the solution evenly at 500 rpm, and after the solution concentration drops to room temperature, add 30 g / L tin (II) sulfate and 60 g / L thiourea. Stir until the solution is clear.

[0031] S3: Preparation of compound crystals: Immerse the copper foam completely in the solution, take it out after staying for 20 minutes, and repeat 30 times by taking out clean copper foam until a large amount of precipitation appears at the bottom of the solution. Use deionized water to clean the bottom precipitation, then use ethanol to wash it, and place it in an oven at 60 ° C for 10 hours to obtain a needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal.

[0032] S4: Ethanol regulates crystal growth: Take the precipitate, add ethanol to cover the precipitate, soak for 30 min, and then centrifuge at a speed of 8000 r / min for 2 min. Extract the precipitate and place it in an oven at 60 °C for vacuum drying for 10 h to obtain copper-containing carbon, nitrogen, oxygen and sulfur compound crystals regulated by ethanol treatment, such as Figure 1 shown.

[0033] S5: Toluene treatment experiment: 0.6 g of the catalyst before ethanol treatment was placed in the fixed bed reactor of the evaluation device. The reaction temperature was 25 °C and the toluene concentration was 200 mg / m3 When the air velocity is 10000 mL / (g·h) and the relative humidity is 30%, the catalytic degradation effect of the catalyst on toluene is as follows: Figure 5 shown.

[0034] Example 2 Copper foil is used as a single copper material to prepare copper-containing carbon, nitrogen, oxygen and sulfur compounds.

[0035] The specific preparation process is as follows: S1: Pretreatment of single copper material: Take copper foil, rinse it with deionized water, and after rinsing it clean, place the copper foil in a cool and ventilated place to allow it to dry naturally.

[0036] S2: Non-metallic raw material solution preparation: Prepare 0.1 mol / L dilute sulfuric acid solution, use a magnetic stirrer to stir the solution evenly at 600 rpm, and after the solution concentration drops to room temperature, add 20 g / L tin (II) sulfate and 50 g / L thiourea. Stir until the solution is clear.

[0037] S3: Preparation of compound crystals: Immerse the copper foil completely in the solution, take it out after staying for 15 minutes, and keep taking out clean copper foil and repeat 20 times until a large amount of precipitation appears at the bottom of the solution. Use deionized water to clean the bottom precipitation, then use ethanol to wash it, place it in an oven at 70 ° C for 12 hours to obtain a needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal.

[0038] Its microscopic appearance is Figure 2 As shown. It can be found that the sample presents needle-shaped crystals, and multiple needle-shaped crystals are piled together to present a loose and porous network structure, which is conducive to the adsorption of reactant molecules and increases the contact area between the catalyst and the reactant molecules, making it easier for the reactants to react under the action of the catalyst.

[0039] Catalyst mapping scan Figure 3 It can be seen that the main components of this needle-shaped crystal are C, N, O, S, and Cu, among which the content of S and Cu elements is relatively high and the distribution is relatively uniform.

[0040] S4: Ethanol regulates crystal growth: take the precipitate, add ethanol to cover the precipitate, soak for 50 min, and then centrifuge at a speed of 7000 r / min for 4 min. Extract the precipitate and place it in an oven at 70 °C for vacuum drying for 12 h to obtain copper-containing carbon-nitrogen-oxygen-sulfur compound crystals after ethanol treatment.

[0041] S5: Toluene treatment experiment: 0.6 g of the catalyst before ethanol treatment was placed in the fixed bed reactor of the evaluation device. The reaction temperature was 25 °C and the toluene concentration was 200 mg / m 3When the air velocity is 10000 mL / (g·h) and the relative humidity is 30%, the catalytic degradation effect of the catalyst on toluene is as follows: Figure 5 shown.

[0042] Example 3 Copper wire is used as a single copper material to prepare copper-containing carbon, nitrogen, oxygen and sulfur compounds.

[0043] The specific preparation process is as follows: S1: Pretreatment of single copper material: Take copper wire, rinse it with deionized water, and place it in a cool and ventilated place to dry it naturally.

[0044] S2: Non-metallic raw material solution preparation: Prepare 0.2 mol / L dilute sulfuric acid solution, use a magnetic stirrer to stir the solution evenly at 700 rpm, and after the solution concentration drops to room temperature, add 10 g / L tin (II) sulfate and 70 g / L thiourea. Stir until the solution is clear.

[0045] S3: Preparation of compound crystals: Immerse the copper wire completely in the solution, take it out after staying for 10 minutes, and repeat 50 times by taking out clean copper wire until a large amount of precipitation appears at the bottom of the solution. Use deionized water to clean the bottom precipitation, then use ethanol to wash it, and place it in an oven at 80 ° C for 9 hours to obtain a needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal.

[0046] S4: Ethanol regulates crystal growth: take the precipitate, add ethanol to cover the precipitate, soak for 45 minutes, and then centrifuge at a speed of 9000 r / min for 5 minutes. Extract the precipitate and place it in an oven at 65 °C for vacuum drying for 10 hours to obtain copper-containing carbon-nitrogen-oxygen-sulfur compound crystals after ethanol treatment.

[0047] Its microscopic appearance is Figure 4 As shown in the figure, after ethanol treatment, the needle-shaped compound structure is transformed into a more regular prismatic crystal structure, indicating that ethanol treatment further regulates the growth of copper-containing carbon-nitrogen-sulfur compound crystals.

[0048] S5: Toluene treatment experiment: 0.6 g of the catalyst before ethanol treatment was placed in the fixed bed reactor of the evaluation device. The reaction temperature was 25 °C and the toluene concentration was 200 mg / m 3 When the air velocity is 10000 mL / (g·h) and the relative humidity is 30%, the catalytic degradation effect of the catalyst on toluene is as follows: Figure 5 shown.

[0049] Example 4 Copper sheets are used as single copper materials to prepare copper-containing carbon, nitrogen, oxygen and sulfur compounds.

[0050] The specific preparation process is as follows: S1: Pretreatment of single copper material: Take a copper sheet, rinse it with deionized water, and after rinsing it clean, place it in a cool and ventilated place to allow it to dry naturally.

[0051] S2: Non-metallic raw material solution preparation: Prepare 0.3 mol / L dilute sulfuric acid solution, use a magnetic stirrer to stir the solution evenly at 600 rpm, and after the solution concentration drops to room temperature, add 40 g / L tin (II) sulfate and 50 g / L thiourea. Stir until the solution is clear.

[0052] S3: Preparation of compound crystals: Immerse the copper sheet completely in the solution, take it out after staying for 5 minutes, and repeat 40 times by taking out clean copper sheets until a large amount of precipitation appears at the bottom of the solution. Wash the bottom precipitation with deionized water, then wash it with ethanol, and place it in an oven at 70 °C for 12 hours to obtain a needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal.

[0053] S4: Ethanol regulates crystal growth: take the precipitate, add ethanol to cover the precipitate, soak for 30 minutes, and then centrifuge at a speed of 8000 r / min for 3 minutes. Extract the precipitate and place it in an oven at 70 °C for vacuum drying for 12 hours to obtain copper-containing carbon-nitrogen-oxygen-sulfur compound crystals after ethanol treatment.

[0054] S5: Toluene treatment experiment: 0.6 g of the catalyst before ethanol treatment was placed in the fixed bed reactor of the evaluation device. The reaction temperature was 25 °C and the toluene concentration was 200 mg / m 3 When the air velocity is 10000 mL / (g·h) and the relative humidity is 30%, the catalytic degradation effect of the catalyst on toluene is as follows: Figure 5 shown.

[0055] Example 5 Zinc (II) chloride is used as a metal salt to prepare copper-containing carbon, nitrogen, oxygen and sulfur compounds.

[0056] The specific preparation process is as follows: S1: Pretreatment of single copper material: Take copper wire, rinse it with deionized water, and place it in a cool and ventilated place to dry it naturally.

[0057] S2: Non-metallic raw material solution preparation: Prepare 0.2 mol / L dilute sulfuric acid solution, use a magnetic stirrer to stir the solution evenly at 700 rpm, and after the solution concentration drops to room temperature, add 30 g / L zinc (II) chloride and 50 g / L thiourea. Stir until the solution is clear.

[0058] S3: Preparation of compound crystals: Immerse the copper wire completely in the solution, take it out after staying for 10 minutes, and repeat 50 times by taking out clean copper wire until a large amount of precipitation appears at the bottom of the solution. Use deionized water to clean the bottom precipitation, then use ethanol to wash it, and place it in an oven at 80 ° C for 9 hours to obtain a needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal.

[0059] S4: Ethanol regulates crystal growth: take the precipitate, add ethanol to cover the precipitate, soak for 45 minutes, and then centrifuge at a speed of 9000 r / min for 5 minutes. Extract the precipitate and place it in an oven at 65 °C for vacuum drying for 10 hours to obtain copper-containing carbon-nitrogen-oxygen-sulfur compound crystals after ethanol treatment.

[0060] S5: Toluene treatment experiment: 0.6 g of the catalyst before ethanol treatment was placed in the fixed bed reactor of the evaluation device. The reaction temperature was 25 °C and the toluene concentration was 200 mg / m 3 When the air velocity is 10000 mL / (g·h) and the relative humidity is 30%, the catalytic degradation effect of the catalyst on toluene is as follows: Figure 5 shown.

[0061] Example 6 Copper foam is used as a single copper material to prepare copper-containing carbon, nitrogen, oxygen and sulfur compounds. The specific preparation process is basically the same as that in Example 1, except that thiourea is replaced by ethylenediaminetetraacetic acid (EDTA). The catalytic degradation effect of the catalyst on toluene is shown in Figure 5 shown.

[0062] Comparative Example 1 The foamed copper is used as a single copper material to prepare copper-containing carbon, nitrogen, oxygen and sulfur compounds. The specific preparation process is basically the same as that of Example 1, except that tin (II) sulfate is not added and no catalyst precipitation is generated in the reaction system.

[0063] Comparative Example 2 The foamed copper is used as a single copper material to prepare copper-containing carbon, nitrogen, oxygen and sulfur compounds. The specific preparation process is basically the same as that in Example 1, except that thiourea is replaced by citric acid, and the catalytic degradation effect of the catalyst on toluene is as follows: Figure 6 As shown in the figure, there is little difference in the first 240 min, but it starts to decrease significantly at 300 min. At 360 min, the removal rate of toluene is only about 23%, which is much lower than that of Example 1 (56.30%). Comparative Example 3 The foamed copper is used as a single copper material to prepare copper-containing carbon, nitrogen, oxygen and sulfur compounds. The specific preparation process is basically the same as that of Example 1, except that the foamed copper is not taken out after being put in, the total immersion time remains unchanged, and the operation is not repeated. Since only a small amount of copper element participates in the reaction, only a very small amount of catalyst precipitation is generated in the reaction system.

[0064] Comparative Example 4 A conventional MOF-supported atomic-level copper-based catalyst was used to treat toluene: 0.6 g of Cu@MOFs catalyst was placed in the fixed-bed reactor of the evaluation device. The reaction temperature was 25 °C and the toluene concentration was 200 mg / m 3 When the air velocity is 10000 mL / (g·h) and the relative humidity is 30%, the catalytic degradation effect of the catalyst on toluene is as follows: Figure 6 shown.

[0065] Comparative Example 5 In this comparative example, copper foam and single copper material are not used to prepare copper-containing carbon, nitrogen, oxygen and sulfur compounds, but copper sulfate solution is directly added. Copper sulfate solution (12 g / L) is added to the non-metallic raw material liquid prepared in Example 1 to form a milky white suspension such as Figure 7 The subsequent treatment of the obtained precipitate is the same as that of Example 1. The SEM images of the precipitates produced in this comparative example and Example 1 are shown in Figure 8 As shown, the mapping surface scan is shown in Fig. 9 It can be seen that the precipitate is in irregular clusters and does not form needle-shaped crystals. The surface scan shows that there is tin element in the precipitate, which is not the target product, and has almost no catalytic degradation effect on toluene.

[0066] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing needle-shaped copper-containing carbon, nitrogen, oxygen and sulfur compound crystals, characterized in that: The preparation method comprises the following steps: S1. Non-metallic raw material liquid configuration: Add a complexing agent and a metal salt to a dilute sulfuric acid solution and stir until the solution is clear to obtain a non-metallic raw material solution; S2. Catalyst preparation: The single copper material is immersed in the non-metallic raw material liquid, stayed there, taken out, and then immersed in a new single copper material, and this step is repeated until a large amount of precipitation appears at the bottom of the non-metallic raw material liquid, thereby obtaining a precipitate, namely, needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystals.

2. The method for preparing the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal according to claim 1, characterized in that: In step S1, the concentration of the dilute sulfuric acid solution is 0.1-1.0 mol / L.

3. The method for preparing the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal according to claim 1, characterized in that: In step S1, the metal salt includes one of tin sulfate, tin chloride, zinc chloride, and nickel sulfate; And / or, the complexing agent includes one of thiourea, ethylenediaminetetraacetic acid, and 2-mercaptobenzimidazole.

4. The method for preparing the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal according to claim 1, characterized in that: In the non-metallic raw material liquid, the amount of metal salt is 10 ~ 100 g / L, and the amount of complexing agent is 10 ~ 70 g / L.

5. The method for preparing the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal according to claim 1, characterized in that: In step S2, the single-element copper material is a material having a single-element copper component on its surface; And / or, the single copper material is a single copper material having a large specific surface area; And / or, the single copper material includes one or more of copper rods, copper wires, copper sheets, copper foils, and foam copper.

6. The method for preparing the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal according to claim 1, characterized in that: In step S2, the dwell time is 5 to 25 min; And / or, the number of repetitions is 10 to 100 times.

7. The method for preparing the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal according to claim 1, characterized in that: In the obtained needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystals, a single needle-shaped crystal is 5 to 10 μm long and 1 to 2 μm wide.

8. The method for preparing the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystal according to claim 1, characterized in that: The needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystals obtained in step S2 are further subjected to ethanol-regulated crystal growth treatment: the precipitate is immersed in ethanol, then centrifuged, and the precipitate is extracted to obtain the precipitate regulated by ethanol treatment, i.e., prismatic copper-containing carbon-nitrogen-oxygen-sulfur compound crystals.

9. The method for preparing the needle-shaped copper-containing carbon-nitrogen-oxygen-sulfur compound crystals according to claim 8, characterized in that: The ethanol soaking time is 10 ~100 min; and / or, the centrifugal treatment time is 2 to 10 min, and the rotation speed is 3000 to 12000 r / min; And / or, in the prismatic copper-containing carbon-nitrogen-oxygen-sulfur compound crystals, the prismatic crystals have a length of 20 to 40 μm and a diameter of 10 to 20 μm.

10. Use of the needle-shaped copper-containing carbon, nitrogen, oxygen and sulfur compound crystals obtained by the preparation method as claimed in claim 1 as a catalyst in ORR, HER, CO2RR and VOCs catalytic degradation.